Comparison of triple phase ct and ultrasonography findings for evaluation of hepatic lesions - Lovely Kaushal; V. K. Verma; Neelam Soni (International Journal of Medical Research and Review, 2016)
Background: Characterizing a hepatic lesion as benign or malignant is essential for correct therapeutic plan and surgical triage. USG plays major role in screening of a liver lesion. Conventional CT with only portal venous phase has certain limitations including its inability to detect lesions which enhances in early arterial phase like HCC and those enhancing in delayed phase like Cholangiocarcinoma. Triphasic CT utilizes three phases and offers a comprehensive and accurate determination.Design: This prospective study included 100 patients with clinical suspicion of hepatic masses.Materials and Methods: All patients underwent both USG and triple phase CT, accuracy, sensitivity and specificity of both the modalities were calculated.Results: USG proved to be a good screening modality with a sensitivity of 82.7% , specificity 95.6 % , PPV 82.7 % and NPV 95.6 % (p value <0.001 , kappa value 0.678) . Triple phase CT is excellent for characterisation and better evaluation of hepatic masses with sensitivity of 91.3%, specificity 97.8 % , PPV 91.3 % and NPV 97.8 % (p value <0.001 , kappa value 0.847). Malignant hepatic lesions can be diagnosed by triphasic CT with accuracy of 93 % , sensitivity and specificity of 93.3 % and 92.5 % respectively and with PPV and NPV of 94.9 % and 90.2 % respectively and by USG with accuracy of 87 % , sensitivity and specificity of 90 % and 82.5 % respectively and PPV and NPV of 88.5 % and 84.6 % respectively.Conclusion: Ultrasonography must be performed in all patients with clinical suspicion of hepatic masses for initial detection and localisation of lesion. Also it is widely available, less expensive and with no radiation exposure. But in comparison to triple phase CT it has lower sensitivity in differentiating benign hepatic lesions from malignant, determining accurate extension of tumor with vascular invasion.